The correct next step is simplifying 2(3-x) by multiplying 2 inside
Step-by-step explanation:
We will solve the equation step by step
Given
3x = 4+2(3 - x)
Multiplying 2 inside bracket
[tex]3x=4+2.3-2.x\\3x=4+6-2x\\3x=10-2x[/tex]
Adding 2x on both sides
[tex]3x+2x=10-2x+2x\\5x=10[/tex]
Dividing both sides by 5
[tex]\frac{5x}{5}=\frac{10}{5}\\x=2[/tex]
The correct next step is simplifying 2(3-x) by multiplying 2 inside
Keywords: Linear equation, Variable
Learn more about linear equation at:
#LearnwithBrainly